KOMPETENSI TENAGA PENYIAR DI LEMBAGA PENYIARAN PUBLIK RADIO REPUBLIK INDONESIA MANADO - FEBRIAN MAIT; FLORENCE LENGKONG; Salmin Dengo (JURNAL ADMINISTRASI PUBLIK, 2023)
Facing the global era, radio managers must improve and reach a standard level, so each broadcasting institution must focus their investment on improving the quality of human resources they have. The competence of every broadcaster in the Radio Republik Indonesia Manado environment is an important key in becoming attractive and selling point. However, there are still some things that have not reached the maximum word. Therefore, this research is proposed to answer questions about the Competence of Broadcasters at the Republic of Indonesia Manado Public Radio Broadcasting Institute. In this study using Gordon's theory, the competence of Broadcasters can be seen based on 6 dimensions which are the benchmarks. Knowledge. Awareness in the cognitive field, a broadcaster knows how to identify learning and how to do good learning. Understanding (Understanding). Cognitive and affective depth possessed by individuals. Ability (Skill). Something that is owned by the individual to carry out the work tasks assigned to him. Value (Value). A standard of behavior that has been believed and is psychologically united in a person. Attitude. Feelings or reactions to a stimulus that comes from outside. Interest (Interest). The tendency of a person to do an act. In this study using a qualitative descriptive research method, namely through interviews with 7 informants in direct observation, and looking for documents related to research assisted by recording devices and writing instruments. The results of this study generally indicate that there is still a need for activities aimed at increasing the competence of existing broadcasters. Keywords : Competency of Broadcasters, Radio Republik Indonesia Manado.